PSIKOLOGI SOSIAL PRASANGKA DAN DISKRIMINASI - Adelia Ananda Putri, Putri Fauziyyah, Jesyinda Putri Wibowo, Zefanya Muri Putri Kristianti, Sulistia (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Prejudice is a negative attitude directed at certain individuals or groups. Prejudice comes from the Latin word prejudice which means a decision that is consistent with previous decisions and experience. Prejudice can also be defined as a negative belief or opinion that causes someone to behave or think in a certain way towards other people. Prejudice has two components, namely the cognitive component (thinking) and the affective component (feeling). Various types of prejudice include sexism, racial prejudice, ageism, the development of prejudice and discrimination. Discrimination is different treatment, differences in treatment can be based on skin color, class or ethnic background, as well as gender, economics, religion, etc. Discrimination is differential treatment due to membership in a particular group or ethnic origin. Then, various types of discrimination such as racism, tokenism and reverse discrimination.